2022
DOI: 10.1016/j.strueco.2021.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of trade to production-Based carbon dioxide emissions

Abstract: International trade and emission offshoring can reduce a country's domestic carbon dioxide emissions, helping it to reach emission reduction targets set under the prevailing territorial climate policy frameworks. We ask what is the net contribution of trade to national production-based emissions. Existing metrics (consumption-based emissions and the technology-adjusted balance of emissions embodied in trade) do not answer this question. Based on global multi-regional input-output tables and the domestic techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 47 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…Wherein the literature concerning emissions could be found in two parts: namely, production‐based emissions (PCO2) and CCO2 in relation to various economic, financial, and environmental indicators. Concerning the former (PCO2), several studies provided empirical evidence and relevant policies to tackle the said issue (Liang et al, 2018; Wang & Zhou, 2020; Wu et al, 2022, among others). However, the empirical literature the CCO2 emissions and its determinants is scant and yet to grow.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Wherein the literature concerning emissions could be found in two parts: namely, production‐based emissions (PCO2) and CCO2 in relation to various economic, financial, and environmental indicators. Concerning the former (PCO2), several studies provided empirical evidence and relevant policies to tackle the said issue (Liang et al, 2018; Wang & Zhou, 2020; Wu et al, 2022, among others). However, the empirical literature the CCO2 emissions and its determinants is scant and yet to grow.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the literature review, it is summarized that most of the previous studies by Sun and Ouyang (2016), Wei et al (2022), Liang et al (2018), Wang and Zhou (2020), and Wu et al (2022), focus on one side of carbon emissions in order to achieve sustainable development goal of the clean environment; however, Adebayo et al (2022), Knight and Schor (2014), Adebayo et al (2021), He et al (2021), Hassan et al (2022), Gyamfi et al (2022), and Kirikkaleli and Oyebanji (2022) focus was also mainly trade adjusted carbon emissions. However, these studies also ignored the role of financial inclusion and environmental taxes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, Kim and Tromp ( 2021 ) investigated carbon emissions embodied in trade in South Korea between 2000 and 2014 by employing MRIO and found significant increases in emissions embodied in exports and imports, which lead to an increase in total emissions in the country. Wu et al ( 2022 ) calculated onshoring and offshoring emissions of 43 countries from 2000 to 2014 by using the Emissions Embodied in Bilateral Trade (EEBT) approach, and found that the main reason for offshoring emissions in the USA and onshoring emissions in China is the trade balance, which is not related to the trade composition. In contrast, Germany and Japan's onshoring emissions are mainly driven by trade composition.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although carbon trading can also increase the price of carbon trading through the crowding-out effect on firms' R&D investments, which in turn discourages green technology innovation, it can still significantly reduce carbon emissions and carbon intensity (Zhang et al, 2022). Whether from a city perspective (Yu et al, 2017), a provincial perspective (Zhang et al, 2021(Zhang et al, ), 10.3389/fevo.2022 or a national perspective (Wu et al, 2022), the evidence of the decoupling effects of economic growth and environmental issues all further confirms the positive effect of foreign trade on the environment. Pu et al (2020) argued that total trade is the main factor driving the growth of carbon emissions.…”
Section: Literature Reviewmentioning
confidence: 99%